Second Language Writing Through Blogs: An Investigation of Learner Autonomy - Behzad Nezakatgoo; Jalil Fathi (Iranian Journal of Applied Language Studies, 2019)
Employing an explanatory sequential design, the present study investigated the effect of English as a Foreign Language (EFL) blog-mediated writing instruction on the students’ learner autonomy. A number of 46 learners who were the students of two intact classes were randomly assigned to control and experimental groups.  Over a 16-week semester, the control group students (n=21) were taught based on regular in-class writing instruction and the students in the experimental group (n=25) made use of blogs in addition to the traditional in-class writing instruction. The data were collected through administering a learner autonomy instrument, consisting of metacognitive, cognitive, social, and affective components, and conducting semi-structured interviews. The results of both quantitative and qualitative data revealed that the blog-mediated writing instruction contributed to enhancing learner autonomy of the participants. More specifically, the students who experienced blog-mediated writing activities showed improvement in metacognitive and cognitive components of learner autonomy. The findings offer significant implications for EFL teachers.